METRIC CHARACTERISTICS OF TESTS BEAR WALK FORWARD AND BACKWARD FOR ASSESSING COORDINATION AND SPEED IN 12-14 YEARS-OLD CHILDREN - Zerin Emić,; Adis Bekrić,; Benjamin Alić,; Almir Atiković,; Muhamed Tabaković, (Sport Scientific And Practical Aspects, 2025)
The aim of this pilot study was to determine the metric characteristics of tests in 12-14 Years-Old Children. For the purpose of this study, a sample of 117 boys was measured. The respondents were selected from two schools in the city of Jelah and Tešanj, Bosnia and Herzegovina. The variables were composed of two motor tests of which two test were for assessing coordination and speed. In accordance with the aforementioned findings, the newly constructed tests can be characterized as a reliable and valid measuring instrument for motor skills assessment of 12-14 year-old children. Also, the test is easy to apply and easy to explain. The body evaluates the motor dimensions, defined as the specific frequency of the upper and lower extremities..